CHALLENGES FACED BY UNACCOMPANIED MINOR-REFUGEES IN SOUTH AFRICA - Magqibelo, Lungile; Londt, Marcel; September, Shiron; Roman, Nicolette (Social Work/Maatskaplike Werk, 2016)
This qualitative study explored the experiences of unaccompanied minor-refugees from Zimbabwe to South Africa. Ten (10) participants, from a shelter in Limpopo Province, were selected using purposive sampling. Five childcare workers also participated. Semi-structured interviews were conducted with the minors and a focus group with the childcare workers to collect the data. Thematic analysis was applied for data analysis. The findings revealed that services by statutory social workers were limited, compared to services by social workers employed in non-governmental organisations. The results highlighted the vulnerability to exploitation and a sense of hopelessness that refugee children experience in South Africa.